Becoming urban: space and mobility amongst Tibetan migrant youths in Lhasa - Costantino, I (2013)
This thesis examines how Tibetan residents of different social backgrounds use and experience the space of the city of Lhasa. I mainly concentrate on young Tibetan rural migrants and document a number of similarities and differences between their spatial practices and those of young Tibetans from urban backgrounds. This thesis shows that my rural migrant informants generally gravitate towards the old quarter of the city, where they practise at religious sites, attend informal private schools, and reside in heavily religious and traditionalist domestic spaces. These spatial practices largely distinguish them from young Tibetans from wealthier families (particularly those of government workers) and who have previously lived in inland China: most often these youths frequent sinicised parts of the city, inhabit domestic spaces lacking religious objects, and are either less interested in or banned from engaging in religious practice. Despite these different orientations, however, the ethnography ultimately shows that a clear-cut distinction between villagers and urbanites cannot be drawn. By looking at both the city of Lhasa and nearby rural villages, the thesis shows that neither the former nor the latter are univocally traditionalist or modernising. Furthermore, informants’ practices both persist and change over time and while throughout the fieldwork some young migrant informants continued in their largely traditionalist engagements within Lhasa’s space, others changed their attitudes and started paying less attention to religion and traditionalist pursuits. To do justice to the changing orientations of my informants, I apply a dynamic theoretical model drawn from practice theory whereby practices and predispositions are shown to be resilient, but not fixed. Ultimately, this thesis proposes that, despite the presence of often-distinct orientations between villagers and urbanites in contemporary Lhasa, all young Tibetans in the city share a common socio-political terrain. In Lhasa, traditionalist predispositions persist, but social mobility, government control, and urbanisation also often lead to the development of more practical, secular, and sinicised attitudes.